UNPACKING RACIOLINGUISTIC IDEOLOGY IN YOUNG ADULT FICTION: A TEXTUAL ANALYSIS OF NOVEL “FRONT DESK” BY KELLY YANG - Nirwana; Saifullah, Aceng Ruhendi; Mustafa, Mutakhirani; Amaliana MZ, Zulfiana (Elite : English and Literature Journal, 2023)
Abstract This study examines the representation of raciolinguistic ideologies in Young Adult Fiction, with a particular focus on Kelly Yang’s novel "Front Desk." The novel, which was published in 2018, serves as a prism through which to examine the interaction between race and language. Raciolinguistic ideologies, as described by Rosa and Flores, pertain to the complex interplay between race and language and how it is actively used to establish and perpetuate social hierarchies and inequalities. This study will use textual analysis to find and examine the linguistic and narrative mechanisms used in "Front Desk" to express and interrogate these raciolinguistic ideologies. The textual analysis results reveal unique linguistic techniques used in "Front Desk," offering light on how characters navigate and negotiate language in connection to their racial identities. The novel’s narrative depictions quietly establish and perpetuate racial hierarchies, providing nuanced insights into how language contributes to these social constructions. The research clarifies the novel’s portrayal of the progression of individuals’ language practices in relation to their racial identities through an examination of character development, providing a greater understanding of raciolinguistic ideologies in narrative form.